Significant deviations in sonographic fetal weight estimation: causes and implications - Krispin, Eyal; Dreyfuss, Elchanan; Fischer, Ofer; Wiznitzer, Arnon; Hadar, Eran; Bardin, Ron (Archives of gynecology and obstetrics, 2020)
Purpose To allocate parameters associated with significant deviations in sonographic estimated fetal weight (EFW) and evaluate labor outcomes in such circumstances. Methods Retrospective case–control study of women with a singleton gestation who underwent sonographic EFW within a week prior to delivery in a single tertiary university-affiliated medical center (2012–2018). The study group was comprised of 177 pregnancies in which sonographic EFW was at least ± 20% of actual birth weight, matched to 354 pregnancies with an accuracy of ± 1% of sonographic EFW to actual birth weight. Matching was based on age, gravidity, parity, and gestational age at delivery. Placental location, fetal presentation, spine position and amniotic fluid volumes during the ultrasound evaluation, as well as pregnancy outcomes, were compared between groups. Results Median gestational age at delivery (37.0 vs. 38.0 weeks, p < 0.001), median estimated fetal weight (2591 vs. 3198 g, p < 0.001) and median birth weight (2916 vs. 3158 g, p = 0.001) were all lower in the non-accurate compared to the accurate weight estimation group. Ultrasound parameters significantly differed between groups. Women in the non-accurate, compared to accurate weight estimations group, presented higher rates of breech presentation (20.34 vs. 9.89%, p = 0.001), lower rates of anterior placenta (44.6 vs. 53.67%, p = 0.002) and lateral spine position (80.23 vs. 88.42%, p < 0.021). Multivariate analysis was utilized to control potential confounders, non-lateral spine position was found to be an independent risk factor for inaccuracies in EFW [OR = 2.505, 95% CI 1.159–5.416, p = 0.0196]. Obstetric parameters did not differ between groups. Higher rates of neonatal intensive care unit admission (20.34 vs. 11.02%, p = 0.003) and neonatal respiratory complications (7.34 vs. 3.39%, p = 0.042) were observed in the non-accurate EFW subgroup. Multivariate analysis demonstrated that inaccuracy in sonographic EFW was an independent risk factor for NICU admission (OR = 2.4, 95% CI 1.034–5.577, p = 0.041). Conclusion Accuracy in sonographic EFW depends on fetal presentation, spine position and placental location. Non-accuracy is associated with adverse neonatal outcomes.